Toc-Thinking Process Approach for Problem Solving in Trademark Registration Process - Birgun, Semra; Erol, Serpil; Alpar, A. Arzu Ceylan (Future Acad, 2019)
Industry 4.0 has caused many changes in commerce as well as in industry. Institutions should therefore revise their strategies and make strategic decisions that will adapt to today's digital world. In the current physical or digital business competition environment, firms want to make their products more attractive by branding and delivering them to large masses. A brand is a feature that separates the product or company from the others and is an advantage both the produces and the consumer. Firms have a wider market share by ensuring the transportation and awareness of its products, and while ensuring its sustainability, consumers can gain prestige, protect their rights, and so on. The trademark must be registered in order to be valid. However, when the application was made in Turkey rejection rate of the brand has increased steadily. This situation causes great waste for the applicant and the applicant institution. In this paper, a study has been conducted with the aim of revealing how problems should be resolved by investigating the causes of rejection of applications and thus increasing the acceptance rate. In this study, Thinking Processes application was made within the framework of the Theory of Constraints approach, which aims to achieve continuous improvement by removing constraints. Thus, it is foreseen that there will be a guide on the possible mistakes of the firm managers who will make a trademark application and how these problems can be resolved. (C) 2019 Published by Future Academy www.FutureAcademy.org .UK
Keywords: Brand; Theory Of Constraints; Trademark Registration; Thinking Processes